Public Event: Brown Bag Lecture Series: Journalisms for Climate Crisis - Ackerley, Christine Rose (Stream: Interdisciplinary Journal of Communication, 2016)
The next Brown Bag Seminar is at noon on March 9th, 2016 at SFU Burnaby in the Mallinson Conference room, K8652. Dr. Shane Gunster and Dr. Robert Hackett, both from the School of Communication will be speaking on the topic of "Journalisms for Climate Crisis". For more information, please see the PDF poster.